AIEE-active blue-emitting molecules derived from methoxyl-decorated triarylcyclopentadienes: Synthesis, crystal structures, photophysical and electroluminescence properties. (December 2017) - Ye, Junwei; Huang, Xueming; Li, Yiwen; Zheng, Ting; Ning, Guiling; Liang, Jie; Liu, Yu; Wang, Yue
Abstract: Five highly efficient blue-emitting triarylcyclopentadiene derivatives1–5 were designed and synthesized by introducing phenyl, methoxyphenyl, methoxybiphenyl and methoxynaphthyl groups to cyclopentadiene backbone, respectively. These compounds possess good thermal stability with decomposition temperatures of 264–340 °C and exhibit intense blue fluorescence with maximum emission peaked at 457–470 nm. All compounds emit weak fluorescence in solution, but they become strong emitters in the aggregated state indicating typical aggregation-induced emission enhancement (AIEE) properties. AIEE behaviour was further confirmed by fluorescent changes depended on temperature and solution viscosity as well as time-resolved fluorescence lifetime measurements. Unexpected substituent effect on aggregation structures and fluorescent properties of1 –5 was also observed. Single-crystal structure analysis revealed that highly twisted conformations and bulky substituents on cyclopentadiene core could dramatically suppress the intermolecular π-π interactions leading to intense blue emission of these compounds in aggregates. Furthermore, the non-doped and doped organic light-emitting diodes (OLEDs) using compounds2 and5 as the emitting layers have been fabricated, respectively. A non-doped OLED with compound5 displays good electroluminescent performance with a light-blue emission and a maximum luminance of 3886 cd/m 2 . Graphical abstract: Five highly efficient AIEE-active blue-emitting triarylcyclopentadiene derivatives were designed and synthesized . AIEE mechanism were investigated by fluorescent changes depended on temperature and solution viscosity as well as time-resolved fluorescence and single-crystal structural analysis. Highlights: Blue-emitting triarylcyclopentadiene derivatives were synthesized. Compounds possess highly twisted conformations. Compounds exhibited aggregation-induced emission enhancement characteristics. A non-doped OLED displays good electroluminescent performance.